PTPN22 is associated with susceptibility to psoriatic arthritis but not psoriasis: evidence for a further PsA-specific risk locus. Issue 10 (28th April 2015) - Bowes, John; Loehr, Sabine; Budu-Aggrey, Ashley; Uebe, Steffen; Bruce, Ian N; Feletar, Marie; Marzo-Ortega, Helena; Helliwell, Philip; Ryan, Anthony W; Kane, David; Korendowych, Eleanor; Alenius, Gerd-Marie; et al.
Abstract : Objectives: Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with psoriasis; it has a higher estimated genetic component than psoriasis alone, however most genetic susceptibility loci identified for PsA to date are also shared with psoriasis. Here we attempt to validate novel single nucleotide polymorphisms selected from our recent PsA Immunochip study and determine specificity to PsA. Methods: A total of 15 single nucleotide polymorphisms were selected (PImmunochip <1×10 −4 ) for validation genotyping in 1177 cases and 2155 controls using TaqMan. Meta-analysis of Immunochip and validation data sets consisted of 3139 PsA cases and 11 078 controls. Novel PsA susceptibility loci were compared with data from two large psoriasis studies (WTCCC2 and Immunochip) to determine PsA specificity. Results: We found genome-wide significant association to rs2476601, mapping to PTPN22 (p=1.49×10 −9, OR=1.32), but no evidence for association in the psoriasis cohort (p=0.34) and the effect estimates were significantly different between PsA and psoriasis (p=3.2×10 −4 ). Additionally, we found genome-wide significant association to the previously reported psoriasis risk loci; NOS2 (rs4795067, p=5.27×10 −9 ). Conclusions: For the first time, we report genome-wide significant association of PTPN22 (rs2476601) to PsA susceptibility, but no evidence for association to psoriasis.